Lecturers’ Experiences of Teaching STEM to Students with Disabilities - Sindile Ngubane-Mokiwa (Commonwealth of Learning, 2016)
Innovative teaching is a concept based on student-centred teaching strategies. Access to Science, Technology, Engineering and Mathematics (STEM) subjects has not been equitable due to use of traditional teaching strategies. These strategies tend to exclude students with disabilities who can effectively learn in environments that appropriately and innovatively integrate technology. Better use of technology in teaching also requires teachers to have the relevant skills to take advantage of the devices in their disposal. This article provides an overview of the literature and experiences of lecturers on the use of technology to facilitate access to STEM subjects at Technical and Vocational Education and Training (TVET) institutions. Using two TVET colleges as case studies, it seeks to clarify how technology is currently used in vocational training. Data gathering was done through in-depth e-interviews and observation of classes. Purposive convenience sampling was used to select the most accessible teachers that teach students with disabilities for this study. Understanding of prior practices and current teacher technological competency are the initial points in the development of TVET technology integration model. In this article, the experiences of teachers were used to guide the development of an inclusive and equitable technology integration model.